KAJIAN YURIDIS TENTANG PARTISIPASI MASYARAKAT DALAM PEMBENTUKAN PERATURAN DAERAH (PERDA) Studi Terhadap Efektifitas Partisipasi Masyarakat Dalam Proses Pembentukan Perda Di Kabupaten Wonosobo - Murkamtoro Prasetyo (UNISSULA Semarang, 2018)
Community participation in the formation of local regulations is very important, because the local regulations formed should be in accordance with the wishes and needs of the community. The effectiveness of community participation in the formation of local regulations will determine the quality, impact and implementation of the local regulations established. However, the participation of the people of Wonosobo Regency in the formation of local regulations is poor. Keywords : Effectiveness, Community Participation, and Local Regulation